2012
DOI: 10.4012/dmj.2012-017
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial analysis of the impact of different manufacturing processes on the marginal fit of zirconia copings

Abstract: This study evaluated the effect of different parameters on the marginal precision of CAD/CAM-fabricated zirconia copings. Specimens (n=60) were fabricated with two different scanners and two milling systems. The copings were evaluated with respect to their mean and average maximum marginal gaps. A two-way analysis of variance (ANOVA) (α=0.05) was used to evaluate the effect of different parameters (scanner, milling process) on marginal accuracy. The mean (averaged maximum) marginal gaps ranged from 57.9 (112.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
37
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 29 publications
3
37
0
2
Order By: Relevance
“…In experiments performed similarly to our experiment, researchers reported marginal gaps in zirconia frames loaded onto the maxillary second molar of 57 to 71 μm 19) , and they also found that zirconia frames for the mandibular first molar, which were made by milling a completely sintered zirconia block using a CAD/CAM system, had marginal gaps of 18 to 58 μm and internal gaps of 105 to 120 μm 20) . The marginal gap values (48.9 to 59.4 μm) and the internal gap values (125.6 to 139.5 μm) obtained in our experiment were close to the results reported in those studies.…”
Section: Discussionsupporting
confidence: 47%
“…In experiments performed similarly to our experiment, researchers reported marginal gaps in zirconia frames loaded onto the maxillary second molar of 57 to 71 μm 19) , and they also found that zirconia frames for the mandibular first molar, which were made by milling a completely sintered zirconia block using a CAD/CAM system, had marginal gaps of 18 to 58 μm and internal gaps of 105 to 120 μm 20) . The marginal gap values (48.9 to 59.4 μm) and the internal gap values (125.6 to 139.5 μm) obtained in our experiment were close to the results reported in those studies.…”
Section: Discussionsupporting
confidence: 47%
“…A previous study demonstrated that the fit of a ceramic restoration may be affected by the milling machine. 26 Perhaps the variation in cement thickness can be attributed to the accuracy of the milling machines. Another limitation in this study is that zirconia restorations did not undergo accelerated aging.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous publications report the adaptation of crown copings made of different materials with an absolute marginal gap ranging from 10 to 110·31 ± 7·22 μm , often with results less than 80 µm . Similarly, the internal gap is between 23·5 ± 7·7 μm and 154·1 ± 10·4 μm in the part axial and between 45·2 ± 15·5 μm and 219.12 ± 87.24 μm in the part occlusal.…”
Section: Discussionmentioning
confidence: 99%